ANALISA KELAYAKAN BISNIS TERHADAP UMKM GILA CEMILAN DALAM MASA PANDEMI COVID 19 - Emliah Hasanah; Deviana Pertiwi; Happy Satrio; Hendra Dwi Prasetya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
During the Covid 19 pandemic, the condition of the Indonesian nation is currently experiencing a period of crisis, especially in the economic sector, which will cause several social problems, such as termination of employment, the number of unemployed is increasing rapidly and employment opportunities are increasingly narrow. The purpose of this journal is to be responsive to costs incurred during production, to calculate net profit and gross profit, as well as whether or not Keripik Uzuz New Normal and Susu Micuare marketed in Sidoarjo and its surrounding areas. The results showed that the average total cost per month was 3,483,000 resulting from a fixed cost of 263,000, 2,134,500 raw material costs for making intestines and 967,500 micu-making raw materials costs, and 118,000 promotion costs. The “Gila Cemilan 3M” business generates a net profit of approximately 917,000 from revenues of 4,400,000 minus an average total cost of 3,483,000. From the calculation of the total cost, it can be known or not the income, expenses and income earned.